Space weathering effects in Diviner Lunar Radiometer multispectral infrared measurements of the lunar Christiansen Feature: Characteristics and mitigation - Lucey, P; Greenhagen, B; Song, E; Arnold, J; Lemelin, M; Donaldson-Hanna, K; Bowles, N; Glotch, T; Paige, D (Elsevier, 2016)
Multispectral infrared measurements by the Diviner Lunar Radiometer Experiment on the Lunar Renaissance Orbiter enable the characterization of the position of the Christiansen Feature, a thermal infrared spectral feature that laboratory work has shown is proportional to the bulk silica content of lunar surface materials. Diviner measurements show that the position of this feature is also influenced by the changes in optical and physical properties of the lunar surface with exposure to space, the process known as space weathering. Large rayed craters and lunar swirls show corresponding Christiansen Feature anomalies. The space weathering effect is likely due to differences in thermal gradients in the optical surface imposed by the space weathering control of albedo. However, inspected at high resolution, locations with extreme compositions and Christiansen Feature wavelength positions – silica-rich and olivine-rich areas – do not have extreme albedos, and fall off the albedo- Christiansen Feature wavelength position trend occupied by most of the Moon. These areas demonstrate that the Christiansen Feature wavelength position contains compositional information and is not solely dictated by albedo. An optical maturity parameter derived from near-IR measurements is used to partly correct Diviner data for space weathering influences.